The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/su9060969
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Promoting Green Building Technologies Adoption in the Construction Industry—An International Study

Abstract: Abstract:Because green building technologies (GBTs) adoption is a promising way of ameliorating the sustainability performance of buildings, GBTs are receiving increased interest in the global construction community. The barriers to the adoption of GBTs, such as higher cost and lack of awareness, further indicate that proper strategies need to be devised for promoting the wider adoption of GBTs in buildings development. However, there exist limited empirical studies identifying the strategies for promoting GBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 59 publications
3
124
0
2
Order By: Relevance
“…The survey implied that precast ratio of 30% received the highest proportion (31.3%). This result revealed that the government policy had a significant effect on promoting prefabrication development [64]. The precast ratio of steel structure systems (80%) was higher than reinforced concrete systems (30%).…”
Section: Discussionmentioning
confidence: 64%
“…The survey implied that precast ratio of 30% received the highest proportion (31.3%). This result revealed that the government policy had a significant effect on promoting prefabrication development [64]. The precast ratio of steel structure systems (80%) was higher than reinforced concrete systems (30%).…”
Section: Discussionmentioning
confidence: 64%
“…From the perspective of the whole life cycle of architecture, researchers study the environmental pollution and other issues [10][11][12][13][14][15]. GBTS include solar systems, green roofs and walls, heat pumps and the application of corresponding technologies throughout the construction project delivery process [8,13,16]. Some GBTS, such as green roofs, solar energy and precast concrete, have been introduced into the development of green projects.…”
mentioning
confidence: 99%
“…Green building (GB), as one of the best practices of sustainable development in the construction industry, has drawn much attention [5][6][7][8]. Many researches of GB have been analyzed from different aspects, for example: Technological innovation [9][10][11], energy saving [12][13][14], risk management [15][16][17][18], influential factors for development [19][20][21], policy incentives and regulations [22][23][24], and economical benefit [25][26][27] etc.…”
Section: Introductionmentioning
confidence: 99%